Analysis of the Relationship between Quality of Financial Statements Review and Audit Findings on the Local Government Financial Statements in Daerah Istimewa Yogyakarta Province, Indonesia - Dwi Windarsih; Irwan Taufiq Ritonga (The Indonesian Journal of Accounting Research, 2017)
Abstract: There are two objectives of this study. The first objective is to evaluate the quality of local government financial statement (LGFS) review conducted by five local government inspectorate offices (i.e., internal auditor) in the Province Daerah Istimewa Yogyakarta, Indonesia. Secondly, this study analyzes the relationship between the quality of LGFS review and the number of audit findings conducted by the Supreme Audit Board (i.e., the external auditor). This study uses qualitative methods. Results of this study indicate that the quality of LGFS review varies significantly among local governments as shown by the score of review quality ranging from 73.08% to 83.59%. Furthermore, the quality of LGFS review has a negative correlation with the number of audit findings, which means that the better the quality of the review the smaller the number of audit findings. Results of this study are expected to provide input to local government inspectorates to take necessary steps so that the implementation of LGFS review to be more qualified. In turn, the number of audit findings can be minimized. Also, the academic benefits of this research are to become a reference for the next researcher who wants to do further research related to the implementation of the LGFS review.Abstrak: Ada dua tujuan dari penelitian ini. Tujuan pertama adalah untuk mengevaluasi kualitas ulasan laporan keuangan pemerintah daerah (LGFS) yang dilakukan oleh lima kantor inspektorat pemerintah daerah (yaitu auditor internal) di Provinsi Daerah Istimewa Yogyakarta, Indonesia. Kedua, studi ini menganalisis hubungan antara kualitas tinjauan LGFS dan jumlah temuan audit yang dilakukan oleh Badan Pemeriksa Keuangan (yaitu auditor eksternal). Penelitian ini menggunakan metode kualitatif. Hasil penelitian ini menunjukkan bahwa kualitas tinjauan LGFS bervariasi secara signifikan di antara pemerintah daerah seperti yang ditunjukkan oleh skor kualitas ulasan mulai dari 73,08% menjadi 83,59%. Selanjutnya, kualitas tinjauan LGFS memiliki korelasi negatif dengan jumlah temuan audit, yang berarti bahwa semakin baik kualitas peninjauan semakin kecil jumlah temuan audit. Hasil penelitian ini diharapkan dapat memberikan masukan kepada inspektorat pemerintah daerah untuk mengambil langkah-langkah yang diperlukan sehingga pelaksanaan tinjauan LGFS menjadi lebih berkualitas. Pada gilirannya, jumlah temuan audit dapat diminimalkan. Selain itu, manfaat akademik dari penelitian ini adalah menjadi referensi bagi peneliti berikutnya yang ingin melakukan penelitian lebih lanjut terkait dengan pelaksanaan tinjauan LGFS.